PERILAKU HERDING PADA SAHAM IPO (INITIAL PUBLIC OFFERING) DI BURSA EFEK INDONESIA - Rahman, Ifal; Widyastuti, Tri; Bahri, Syamsul (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Herding behavior is a phenomenon that occurs when a group moves as a unit with irrational motives. Spontaneously, it can be caused by collective emotions arising from extreme social shock, or it can be manipulated by people who have the expertise to lead in the same direction. This study aims to analyze the effect of market returns on the spread of returns as measured by the Cross-Sectional Absolute Standard (CSSD) and Cross-Sectional Absolute Deviation (CSAD) methods and to find out indications of herding on the Indonesian Stock Exchange for the 2020-2021 period. The population used in this study is 104 companies that have conducted IPOs from 2020-2021. The results show that the independent variable market returns has a positive and significant influence on the dependent variable on the spread of returns as measured by the Cross-Sectional Absolute Standard (CSSD) method and Cross-Sectional Absolute Deviation (CSAD). During the observation period, there were no indications of herding behavior occurring in 2020-2021.